Efficacy and safety of focal pulsed-field ablation for ventricular arrhythmias: two-centre experience - Peichl, Petr; Bulava, Alan; Wichterle, Dan; Schlosser, Filip; Stojadinović, Predrag; Borišincová, Eva; Štiavnický, Peter; Hašková, Jana; Kautzner, Josef (Europace, 2024)
AIMS: A pulsed electric field (PF) energy source is a novel potential option for catheter ablation of ventricular arrhythmias (VAs) as it can create deeper lesions, particularly in scarred tissue. However, very limited data exist on its efficacy and safety. This prospective observational study reports the initial experience with VA ablation using focal PF. METHODS AND RESULTS: The study population consisted of 44 patients (16 women, aged 61 ± 14years) with either frequent ventricular premature complexes (VPCs, 48%) or scar-related ventricular tachycardia (VT, 52%). Ablation was performed using an irrigated 4 mm tip catheter and a commercially available PF generator. On average, 16 ± 15 PF applications (25 A) were delivered per patient. Acute success was achieved in 84% of patients as assessed by elimination of VPC or reaching non-inducibility of VT. In three cases (7%), a transient conduction system block was observed during PF applications remotely from the septum. Root analysis revealed that this event was caused by current leakage from the proximal shaft electrodes in contact with the basal interventricular septum. Acute elimination of VPC was achieved in 81% patients and non-inducibility of VT in 83% patients. At the 3-month follow-up, persistent suppression of the VPC was confirmed on Holter monitoring in 81% patients. In the VT group, the mean follow-up was 116 ± 75 days and a total of 52% patients remained free of any VA. CONCLUSION: Pulsed electric field catheter ablation of a broad spectrum of VA is feasible with acute high efficacy; however, the short-term follow-up is less satisfactory for patients with scar-related VT.
Keywords: výsledek terapie; jizva; Male; Tachycardia, Ventricular; Cicatrix; Aged; Prospective Studies; mužské pohlaví; senioři; Catheter Ablation; komorové extrasystoly; Treatment Outcome; Ventricular premature complexes; lidé; Ventricular tachycardia; ženské pohlaví; Humans; Ventricular Premature Complexes; Electrophysiologic Techniques, Cardiac; elektrofyziologické techniky kardiologické; katetrizační ablace; Female; Catheter ablation; Pulsed-field energy; lidé středního věku; komorová tachykardie; Middle Aged; prospektivní studie